THE EFFECT OF CTL APPROACH ON SCIENCE LEARNING OUTCOMES IN STUDENTS OF CLASS V SDN 09 AIR PACAH CITY OF PADANG - sry apfani; Fadhlil Azhim (LP2M Universitas Adzkia, 2021)
The background of the problem in the teacher's research has not used the Contextual Teaching & Learning approach in learning. In learning the teacher still tends to verbalism, in the learning process it does not look attractive, and student learning outcomes are still low. This study aims to determine the effect of using the Contextual Teaching & Learning approach on student learning outcomes in science learning with the material adaptation of plants in class V SDN 09 Air Pacah Padang City. This research is a Quasi Experimental Design with Posttest-Only-Design. The subjects of this study were the fifth grade students of SDN 09 Air Pacah Padang City where the VA class was the experimental class using a contextual teaching & learning approach, while the VB class was the control class using conventional learning or without using the Contextual Teaching & Learning approach. Data collection in this study is in the form of learning outcomes tests in the form of objective questions as many as 15 questions. The data obtained were analyzed using the t test. Based on the results of testing for normality and homogeneity of the data obtained from the experimental group and the control group, the distribution was normal and homogeneous. Subsequently, the hypothesis was tested with a t-test and showed tcount = 2,553. and ttable = 1,680 with db = (n1 + n2) – 2 = 23 + 23 - 2 = 44 and a significant level of 5%. Based on the test tcount > ttable (> 1.680) then H0 is rejected and H1 is accepted with the conclusion,